High-strength inorganic fiberboard and preparation method thereof

By using microfiber glass wool, polycrystalline mullite fiber, ceramic fiber, and silica-coated calcium sulfate whiskers and polyvinyl alcohol composite metal oxide as binder components, the problem of insufficient strength of inorganic fiberboard was solved, and high-strength and durable inorganic fiberboard was prepared.

CN121405403APending Publication Date: 2026-01-27LANGFANG KEILUO NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511701393.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-19
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

Existing inorganic fiberboards suffer from insufficient strength, easy breakage, and cracking when using silica sol as a binder.

Method used

The inorganic fiberboard uses microfiber glass wool, polycrystalline mullite fiber, and ceramic fiber as the main raw materials, and adds silica-coated calcium sulfate whiskers and polyvinyl alcohol composite metal oxide as binder components to improve the compatibility and dispersibility of the binder and increase the strength of the inorganic fiberboard.

Benefits of technology

It significantly improves the overall strength, dimensional stability and durability of inorganic fiberboard, improves the cracking and breakage problems that easily occur when using silica sol as a binder, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of fiberboards, and provides a high-strength inorganic fiberboard and a preparation method thereof. The high-strength inorganic fiberboard is prepared from the following raw material components: microfiber glass wool, polycrystalline mullite fibers, ceramic fibers and an adhesive, the adhesive is prepared from the following raw material components: silica sol, an anti-settling agent, a coupling agent, metal oxide, calcium sulfate whiskers and water; the calcium sulfate whisker is silicon dioxide coated calcium sulfate whisker, and / or the metal oxide is polyvinyl alcohol composite metal oxide. According to the technical scheme, the problem that the strength of the inorganic fiberboard is insufficient when silica sol is used as a binder in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fiberboard technology, specifically to a high-strength inorganic fiberboard and its preparation method. Background Technology

[0002] Inorganic fiberboard is a type of engineered wood product, made primarily from fibrous materials, with the addition of binders and hot-pressed processing. It possesses properties such as fire resistance, heat insulation, thermal insulation, lightweight, and sound absorption / insulation. The binders fall into two main categories: organic binders, such as carboxymethyl cellulose, polyvinyl alcohol, and resins, and inorganic binders, such as water glass and silica sol.

[0003] Silica sol is widely used due to its low cost, good adhesion, and high fire resistance and insulation properties. However, it also has the following drawbacks during use: as moisture evaporates, it shrinks significantly, making it prone to breakage and cracking, resulting in insufficient strength of the inorganic fiberboard. Summary of the Invention

[0004] This invention proposes a high-strength inorganic fiberboard and its preparation method, which solves the problem of insufficient strength of inorganic fiberboard when silica sol is used as a binder in related technologies.

[0005] The technical solution of the present invention is as follows: A high-strength inorganic fiberboard, the raw materials of which include the following components: microfiber glass wool, polycrystalline mullite fiber, ceramic fiber and adhesive; The raw materials for the adhesive include the following components: silica sol, anti-settling agent, coupling agent, metal oxide, calcium sulfate whiskers, and water; The calcium sulfate whiskers are silica-coated calcium sulfate whiskers, and / or the metal oxide is a polyvinyl alcohol composite metal oxide.

[0006] As a further technical solution, the mass ratio of the microfiber glass wool, polycrystalline mullite fiber, and ceramic fiber is 1:4:5 to 2:3:5.

[0007] In the inorganic fiberboard of this invention, microfiber glass wool possesses lightweight, high strength, high temperature resistance, excellent thermal insulation, and corrosion resistance. Its addition significantly improves the overall strength, dimensional stability, and durability of the inorganic fiberboard. Polycrystalline mullite fiber has excellent high-temperature stability, low thermal conductivity, good thermal shock resistance, and good chemical inertness. Its addition enhances the fire resistance and mechanical strength of the inorganic fiberboard and extends its service life. Ceramic fiber has high temperature resistance, acid and alkali corrosion resistance, and good chemical stability. Its addition improves the fire resistance and service life of the inorganic fiberboard.

[0008] As a further technical solution, the mass ratio of the silica sol, anti-settling agent, coupling agent, metal oxide, calcium sulfate whiskers and water is 15~25:0.5~1:1.5:8~12:10:60.

[0009] As a further technical solution, when the calcium sulfate whiskers are silica-coated calcium sulfate whiskers, the silica-coated calcium sulfate whiskers are prepared by the sol-gel method.

[0010] As a further technical solution, when the calcium sulfate whiskers are silica-coated calcium sulfate whiskers, the preparation method of the silica-coated calcium sulfate whiskers includes the following steps: S1. Disperse calcium sulfate whiskers in water to obtain a suspension; S2. After mixing the suspension, ammonia and isopropanol, tetraethyl orthosilicate is added while stirring to carry out the reaction. The product is centrifuged, washed with water and dried to obtain silica-coated calcium sulfate whiskers.

[0011] The method for preparing silica-coated calcium sulfate whiskers provided by this invention produces silica-coated calcium sulfate whiskers with a core-shell structure, where the core is a calcium sulfate whisker and the shell is silica. When added to an adhesive, the whiskers exhibit good dispersibility and can significantly improve the strength of inorganic fiberboard.

[0012] As a further technical solution, when the metal oxide is a polyvinyl alcohol composite metal oxide, the polyvinyl alcohol composite metal oxide includes one or two of polyvinyl alcohol-coated metal oxide, polyvinyl alcohol, and metal oxide nanofibers.

[0013] As a further technical solution, when the polyvinyl alcohol composite metal oxide includes a polyvinyl alcohol-coated metal oxide, the preparation method of the polyvinyl alcohol-coated metal oxide includes the following steps: Polyvinyl alcohol was dissolved in water, and metal oxides were added and ultrasonically dispersed evenly. The mixture was then filtered and dried to obtain polyvinyl alcohol coated with metal oxides.

[0014] As a further technical solution, the raw materials for the polyvinyl alcohol-coated metal oxide include polyvinyl alcohol, metal oxide and water in a mass ratio of 1~15:8:100.

[0015] As a further technical solution, the polyvinyl alcohol composite metal oxide is polyvinyl alcohol and metal oxide nanofibers, which are prepared by electrospinning.

[0016] In this invention, the addition of polyvinyl alcohol and metal oxide nanofibers further improves the strength of the inorganic fiberboard. Because of the gaps between the fibers in the polyvinyl alcohol and metal oxide nanofibers, other components of the adhesive can penetrate, allowing for thorough mixing. Simultaneously, the metal oxide phase is uniformly dispersed within the polyvinyl alcohol phase and interacts with each other. This avoids the problem of poor metal oxide dispersion in traditional direct mixing processes, and also avoids the following problems that occur in the impregnation and coating modification preparation of polyvinyl alcohol-coated metal oxides: ① When the concentration of polyvinyl alcohol in the polyvinyl alcohol coating solution is too high, the coating layer becomes too thick and clumps, hindering thorough mixing with other components of the adhesive. If the clumps of polyvinyl alcohol-coated metal oxides are ground and refined, the polyvinyl alcohol coating layer will peel off, ultimately limiting the effect of improving the strength of the inorganic fiberboard. ② When the polyvinyl alcohol concentration in the polyvinyl alcohol coating solution is too low, the coating layer is thin. Due to the insufficient amount of polyvinyl alcohol in the polyvinyl alcohol-coated metal oxide, the flexibility of the adhesive film is limited. The improvement effect on the problem of easy breakage and cracking of silica sol as a binder is not obvious, and ultimately the effect of improving the strength of inorganic fiberboard is limited.

[0017] As a further technical solution, during electrospinning, the voltage is 16~22kV, the feed speed is 0.0015~0.002mm / s, and the receiving distance is 15~20cm.

[0018] As a further technical solution, the raw materials for the polyvinyl alcohol and metal oxide nanofibers include polyvinyl alcohol, metal oxide and water in a mass ratio of 15:5 to 8:100.

[0019] As a further technical solution, the metal oxide includes one or both of zirconium dioxide and chromium dioxide.

[0020] As a further technical solution, the preparation method of the polyvinyl alcohol and metal oxide nanofibers includes the following steps: dissolving polyvinyl alcohol in water, adding metal oxide and ultrasonically dispersing it evenly to obtain an electrospinning solution, electrospinning the electrospinning solution, and drying it to obtain polyvinyl alcohol and metal oxide nanofibers.

[0021] As a further technical solution, the mass of the adhesive is 5% to 8% of the combined mass of the microfiber glass wool, polycrystalline mullite fiber, and ceramic fiber.

[0022] As a further technical solution, the anti-settling agent includes one or more of RHEOBYK-405, RHEOBYK-410, and RHEOBYK-420.

[0023] As a further technical solution, the coupling agent includes one or more of epoxy silane, amino silane, and mercapto silane, preferably amino silane, and more preferably KH-550.

[0024] This invention also proposes a method for preparing a high-strength inorganic fiberboard, comprising the following steps: A1. After crushing the microfiber glass wool, polycrystalline mullite fiber and ceramic fiber respectively, mix them evenly to obtain fibrous material; A2. After mixing the raw materials of the adhesive evenly, the adhesive is obtained; A3. Mix the adhesive with the fibrous material, press and mold, bake, and cool to obtain a high-strength inorganic fiberboard.

[0025] The working principle and beneficial effects of this invention are as follows: This invention improves the strength of inorganic fiberboard by adding silica-coated calcium sulfate whiskers and / or polyvinyl alcohol-composite metal oxides. The reasons are as follows: ① Silica coating not only enhances the modification effect of the coupling agent in the adhesive on the calcium sulfate whiskers but also improves the compatibility between the calcium sulfate whiskers and silica sol. The addition of silica-coated calcium sulfate whiskers not only increases the strength of the adhesive but also acts as a skeleton within it, mitigating the problem of silica sol easily breaking and cracking as a binder. ② Polyvinyl alcohol-composite metal oxides improve their dispersibility and compatibility in the adhesive. The introduction of polyvinyl alcohol also improves the flexibility of the adhesive film after formation, further mitigating the problem of silica sol easily breaking and cracking as a binder. Ultimately, this achieves the effect of improving the strength of the inorganic fiberboard. Detailed Implementation

[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0027] The parameters of the raw materials in the following examples and comparative examples are as follows: Silica sol: 30% silica by mass; Polyvinyl alcohol: weight average molecular weight is 140,000; Zirconium dioxide: Particle size 30nm; Microfiber glass wool: purchased from Shanxi Huakang Green Building Materials Co., Ltd.; Polycrystalline mullite fibers: average diameter 3μm; Ceramic fibers: average diameter 3μm; Calcium sulfate whiskers: average diameter 4μm, average length 125μm; Needle tube: The spinning needle is model 23G, with an inner diameter of 0.33mm and an outer diameter of 0.63mm.

[0028] Example 1 (1) Preparation of polyvinyl alcohol coated metal oxide: 15 parts of polyvinyl alcohol were dissolved in 100 parts of water, and 8 parts of zirconium dioxide were added. The mixture was ultrasonically dispersed at a power of 200W, a frequency of 30kHz, a temperature of 50℃, and a time of 30min. After being evenly dispersed, the mixture was filtered and dried to obtain polyvinyl alcohol coated metal oxide. (2) Preparation of inorganic fiberboard: 10 parts of microfiber glass wool, 40 parts of polycrystalline mullite fiber and 50 parts of ceramic fiber were crushed and mixed evenly to obtain fibrous material; 20 parts of silica sol, 0.5 parts of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 8 parts of polyvinyl alcohol coated metal oxide, 10 parts of calcium sulfate whiskers and 60 parts of water were mixed evenly to obtain adhesive; 8 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked and cooled to obtain inorganic fiberboard.

[0029] Example 2 (1) Preparation of polyvinyl alcohol coated metal oxide: 1 part of polyvinyl alcohol was dissolved in 100 parts of water, and 8 parts of zirconium dioxide were added. The ultrasonic power was 100W, the ultrasonic frequency was 20kHz, the ultrasonic temperature was 60℃, and the ultrasonic time was 20min. After the mixture was evenly dispersed, it was filtered and dried to obtain polyvinyl alcohol coated metal oxide. (2) Preparation of inorganic fiberboard: 15 parts of microfiber glass wool, 35 parts of polycrystalline mullite fiber and 50 parts of ceramic fiber were crushed and mixed evenly to obtain fibrous material; 25 parts of silica sol, 0.8 parts of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 12 parts of polyvinyl alcohol coated metal oxide, 10 parts of calcium sulfate whiskers and 60 parts of water were mixed evenly to obtain adhesive; 8 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked and cooled to obtain inorganic fiberboard.

[0030] Example 3 (1) Preparation of polyvinyl alcohol coated metal oxide: 15 parts of polyvinyl alcohol were dissolved in 100 parts of water, and 8 parts of zirconium dioxide were added. The ultrasonic power was 300W, the ultrasonic frequency was 20kHz, the ultrasonic temperature was 50℃, and the ultrasonic time was 25min. After the mixture was evenly dispersed, it was filtered, dried, and ground to obtain polyvinyl alcohol coated metal oxide. (2) Preparation of inorganic fiberboard: 20 parts of microfiber glass wool, 30 parts of polycrystalline mullite fiber and 50 parts of ceramic fiber were crushed and mixed evenly to obtain fibrous material; 15 parts of silica sol, 1 part of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 10 parts of polyvinyl alcohol coated metal oxide, 10 parts of calcium sulfate whiskers and 60 parts of water were mixed evenly to obtain adhesive; 8 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked and cooled to obtain inorganic fiberboard.

[0031] Example 4 (1) Preparation of polyvinyl alcohol and metal oxide nanofibers: 15 parts of polyvinyl alcohol were dissolved in 100 parts of water, and 8 parts of zirconium dioxide were added. The ultrasonic power was 200W, the ultrasonic frequency was 30kHz, the ultrasonic temperature was 50℃, and the ultrasonic time was 30min. After the mixture was evenly dispersed, it was transferred to a needle tube and placed on an electrospinning device. The voltage was set to 16kV, the feed speed was 0.0015mm / s, and the receiving distance was 15cm for electrospinning. The electrospinned membrane was collected and dried to obtain polyvinyl alcohol and metal oxide nanofibers. (2) Preparation of inorganic fiberboard: 10 parts of microfiber glass wool, 40 parts of polycrystalline mullite fiber and 50 parts of ceramic fiber were crushed and mixed evenly to obtain fibrous material; 20 parts of silica sol, 0.5 parts of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 8 parts of polyvinyl alcohol and metal oxide nanofiber, 10 parts of calcium sulfate whiskers and 60 parts of water were mixed evenly to obtain adhesive; 8 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked and cooled to obtain inorganic fiberboard.

[0032] Example 5 (1) Preparation of polyvinyl alcohol and metal oxide nanofibers: 15 parts of polyvinyl alcohol were dissolved in 100 parts of water, and 8 parts of zirconium dioxide were added. The ultrasonic power was 100W, the ultrasonic frequency was 20kHz, the ultrasonic temperature was 60℃, and the ultrasonic time was 20min. After the mixture was evenly dispersed, it was transferred to a needle tube and placed on an electrospinning device. The voltage was set to 20kV, the feed speed was 0.0018mm / s, and the receiving distance was 18cm for electrospinning. The electrospinned membrane was collected and dried to obtain polyvinyl alcohol and metal oxide nanofibers. (2) Preparation of inorganic fiberboard: 15 parts of microfiber glass wool, 35 parts of polycrystalline mullite fiber and 50 parts of ceramic fiber were crushed and mixed evenly to obtain fibrous material; 25 parts of silica sol, 0.8 parts of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 12 parts of polyvinyl alcohol and metal oxide nanofiber, 10 parts of calcium sulfate whiskers and 60 parts of water were mixed evenly to obtain adhesive; 8 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked and cooled to obtain inorganic fiberboard.

[0033] Example 6 (1) Preparation of polyvinyl alcohol and metal oxide nanofibers: 15 parts of polyvinyl alcohol were dissolved in 100 parts of water, and 8 parts of zirconium dioxide were added. The ultrasonic power was 300W, the ultrasonic frequency was 20kHz, the ultrasonic temperature was 50℃, and the ultrasonic time was 25min. After the mixture was evenly dispersed, it was transferred to a needle tube and placed on an electrospinning device. The voltage was set to 22kV, the feed speed was 0.002mm / s, and the receiving distance was 20cm for electrospinning. The electrospinned film was collected and dried to obtain polyvinyl alcohol and metal oxide nanofibers. (2) Preparation of inorganic fiberboard: 20 parts of microfiber glass wool, 30 parts of polycrystalline mullite fiber and 50 parts of ceramic fiber were crushed and mixed evenly to obtain fibrous material; 15 parts of silica sol, 1 part of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 10 parts of polyvinyl alcohol and metal oxide nanofiber, 10 parts of calcium sulfate whiskers and 60 parts of water were mixed evenly to obtain adhesive; 8 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked and cooled to obtain inorganic fiberboard.

[0034] Example 7 (1) Preparation of silica-coated calcium sulfate whiskers: Calcium sulfate whiskers were dispersed in water to obtain a 4.5 wt% suspension; 0.5 parts of ammonia and 20 parts of isopropanol were added to 45 parts of the suspension and mixed for 30 min. Then, tetraethyl orthosilicate was added while stirring at 1500 rpm. The amount of tetraethyl orthosilicate added was 10 mmol / L. The reaction was carried out at room temperature for 24 h. The product was centrifuged, washed with water, and dried to obtain silica-coated calcium sulfate whiskers. (2) Preparation of inorganic fiberboard: 10 parts of microfiber glass wool, 40 parts of polycrystalline mullite fiber and 50 parts of ceramic fiber were crushed and mixed evenly to obtain fibrous material; 20 parts of silica sol, 0.5 parts of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 8 parts of zirconium dioxide, 10 parts of silica-coated calcium sulfate whiskers and 60 parts of water were mixed evenly to obtain adhesive; 8 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked and cooled to obtain inorganic fiberboard.

[0035] Example 8 (1) Preparation of polyvinyl alcohol and metal oxide nanofibers: 15 parts of polyvinyl alcohol were dissolved in 100 parts of water, and 8 parts of zirconium dioxide were added. The ultrasonic power was 200W, the ultrasonic frequency was 30kHz, the ultrasonic temperature was 50℃, and the ultrasonic time was 30min. After the mixture was evenly dispersed, it was transferred to a needle tube and placed on an electrospinning device. The voltage was set to 16kV, the feed speed was 0.0015mm / s, and the receiving distance was 15cm for electrospinning. The electrospinned membrane was collected and dried to obtain polyvinyl alcohol and metal oxide nanofibers. (2) Preparation of silica-coated calcium sulfate whiskers: Calcium sulfate whiskers were dispersed in water to obtain a 4.5 wt% suspension; 0.5 parts of ammonia and 20 parts of isopropanol were added to 45 parts of the suspension and mixed for 30 min. Then, tetraethyl orthosilicate was added while stirring at 1500 rpm. The amount of tetraethyl orthosilicate added was 10 mmol / L. The reaction was carried out at room temperature for 24 h. The product was centrifuged, washed with water, and dried to obtain silica-coated calcium sulfate whiskers. (3) Preparation of inorganic fiberboard: 10 parts of microfiber glass wool, 40 parts of polycrystalline mullite fiber and 50 parts of ceramic fiber were crushed and mixed evenly to obtain fibrous material; 20 parts of silica sol, 0.5 parts of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 8 parts of polyvinyl alcohol and metal oxide nanofiber, 10 parts of silica-coated calcium sulfate whiskers and 60 parts of water were mixed evenly to obtain adhesive; 8 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked and cooled to obtain inorganic fiberboard.

[0036] Example 9 (1) Preparation of polyvinyl alcohol and metal oxide nanofibers: 15 parts of polyvinyl alcohol were dissolved in 100 parts of water, and 5 parts of zirconium dioxide were added. The ultrasonic power was 100W, the ultrasonic frequency was 20kHz, the ultrasonic temperature was 50℃, and the ultrasonic time was 40min. After the mixture was evenly dispersed, it was transferred to a needle tube and placed on an electrospinning device. The voltage was set to 22kV, the feed speed was 0.002mm / s, and the receiving distance was 20cm for electrospinning. The electrospinned film was collected and dried to obtain polyvinyl alcohol and metal oxide nanofibers. (2) Preparation of silica-coated calcium sulfate whiskers: Calcium sulfate whiskers were dispersed in water to obtain a 4.5 wt% suspension; 0.5 parts of ammonia and 20 parts of isopropanol were added to 45 parts of the suspension and mixed for 30 min. Then, tetraethyl orthosilicate was added while stirring at 1500 rpm. The amount of tetraethyl orthosilicate added was 10 mmol / L. The reaction was carried out at room temperature for 24 h. The product was centrifuged, washed with water, and dried to obtain silica-coated calcium sulfate whiskers. (3) Preparation of inorganic fiberboard: 20 parts of microfiber glass wool, 30 parts of polycrystalline mullite fiber and 50 parts of ceramic fiber were crushed and mixed evenly to obtain fibrous material; 20 parts of silica sol, 0.8 parts of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 10 parts of polyvinyl alcohol and metal oxide nanofiber, 10 parts of silica-coated calcium sulfate whiskers and 60 parts of water were mixed evenly to obtain adhesive; 5 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked and cooled to obtain inorganic fiberboard.

[0037] Comparative Example 1 Preparation of inorganic fiberboard: 10 parts of microfiber glass wool, 40 parts of polycrystalline mullite fiber, and 50 parts of ceramic fiber were pulverized and mixed evenly to obtain fibrous material; 20 parts of silica sol, 0.5 parts of anti-settling agent RHEOBYK-405, 1.5 parts of coupling agent KH-550, 8 parts of zirconium dioxide, 10 parts of calcium sulfate whiskers, and 60 parts of water were mixed evenly to obtain adhesive; 8 parts of adhesive and 100 parts of fibrous material were mixed, pressed into shape, demolded, baked, and cooled to obtain inorganic fiberboard.

[0038] Performance testing: (1) Perpendicular tensile strength: The test shall be conducted in accordance with the method in GB / T 30804-2014. The sample size is: 200mm long × 200mm wide × 50mm thick. (2) Compressive strength: The test shall be conducted in accordance with the method in GB / T 13480-2014. The sample size is: 200mm long × 200mm wide × 50mm thick. The test results are recorded in Table 1.

[0039] Table 1 Performance test results of inorganic fiberboard

[0040] As shown in Table 1, the inorganic fiberboard provided by this invention exhibits a tensile strength perpendicular to the surface of over 57.4 kPa and a compressive strength of 49.2 kPa, demonstrating high strength. Furthermore, the inorganic fiberboards obtained in Examples 1-9 show higher tensile and compressive strengths perpendicular to the surface than those in Comparative Example 1, indicating that the addition of silica-coated calcium sulfate whiskers and / or polyvinyl alcohol composite metal oxides improves the strength of the inorganic fiberboard.

[0041] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-strength inorganic fiberboard, characterized in that, The raw materials include the following components: microfiber glass wool, polycrystalline mullite fiber, ceramic fiber, and adhesive; The raw materials for the adhesive include the following components: silica sol, anti-settling agent, coupling agent, metal oxide, calcium sulfate whiskers, and water; The calcium sulfate whiskers are silica-coated calcium sulfate whiskers, and / or the metal oxide is a polyvinyl alcohol composite metal oxide.

2. The high-strength inorganic fiberboard according to claim 1, characterized in that, When the calcium sulfate whiskers are silica-coated calcium sulfate whiskers, the silica-coated calcium sulfate whiskers are prepared by the sol-gel method.

3. The high-strength inorganic fiberboard according to claim 1, characterized in that, When the calcium sulfate whiskers are silica-coated calcium sulfate whiskers, the preparation method of the silica-coated calcium sulfate whiskers includes the following steps: S1. Disperse calcium sulfate whiskers in water to obtain a suspension; S2. After mixing the suspension, ammonia and isopropanol, tetraethyl orthosilicate is added while stirring to carry out the reaction. The product is centrifuged, washed with water and dried to obtain silica-coated calcium sulfate whiskers.

4. The high-strength inorganic fiberboard according to claim 1, characterized in that, When the metal oxide is a polyvinyl alcohol composite metal oxide, the polyvinyl alcohol composite metal oxide includes one or two of polyvinyl alcohol-coated metal oxides, polyvinyl alcohol, and metal oxide nanofibers.

5. A high-strength inorganic fiberboard according to claim 4, characterized in that, The polyvinyl alcohol composite metal oxide is composed of polyvinyl alcohol and metal oxide nanofibers, which are prepared by electrospinning.

6. A high-strength inorganic fiberboard according to claim 5, characterized in that, During electrospinning, the voltage is 16~22kV, the feed speed is 0.0015~0.002mm / s, and the receiving distance is 15~20cm.

7. A high-strength inorganic fiberboard according to claim 5, characterized in that, The raw materials for the polyvinyl alcohol and metal oxide nanofibers include polyvinyl alcohol, metal oxides and water in a mass ratio of 15:5 to 8:

100.

8. A high-strength inorganic fiberboard according to claim 1, characterized in that, The metal oxide includes one or both of zirconium dioxide and chromium dioxide.

9. A high-strength inorganic fiberboard according to claim 5, characterized in that, The preparation method of the polyvinyl alcohol and metal oxide nanofibers includes the following steps: dissolving polyvinyl alcohol in water, adding metal oxide and ultrasonically dispersing it evenly to obtain an electrospinning solution, electrospinning the electrospinning solution, and drying it to obtain polyvinyl alcohol and metal oxide nanofibers.

10. A method for preparing a high-strength inorganic fiberboard, used to prepare the high-strength inorganic fiberboard according to any one of claims 1 to 9, characterized in that, Includes the following steps: A1. After crushing the microfiber glass wool, polycrystalline mullite fiber and ceramic fiber respectively, mix them evenly to obtain fibrous material; A2. After mixing the raw materials of the adhesive evenly, the adhesive is obtained; A3. Mix the adhesive with the fibrous material, press and mold, bake, and cool to obtain a high-strength inorganic fiberboard.

Citation Information

Patent Citations

  • Ceramic fiber plate and preparation method thereof

    CN104446222A

  • Modified calcium sulfate whisker and polyurethane composite foam material and preparation process thereof

    CN110423326A

  • Fire-resistant inorganic fiber cotton board and preparation method thereof

    CN120664852A

  • Manufacture of heat resistant inorganic fiber formed body

    JP1988112478A

  • Inorganic fiber molded form and manufacture thereof

    JP1996174687A